Supplier selection model for decision making in railway information system - Jayakrishnan, Mailasan (2022)
In today's world, the decision-making process is widely used as it facilitates decision-makers to perform strategized solutions for various kinds of scenarios in organizations. In this case, the decision-making process is required to be executed in the supplier selection requirements for railway supplier selection, due to poorly specified supplier requirements. Supplier errors will produce a defective selection process that can lead to undesirable performance, extensive rework costs, and lead to railway project delays or failures. To avoid this problem, early identification of supplier selection requirements must be performed to eliminate supplier requirements errors and ensure that all decision-making has achieved appropriate supplier selection quality level before moving to the next phase of the decision-making process. Motivated from these problems, the objectives of this study are three-fold; 1) to analyze the supplier requirements characteristic for the decision-making process in the railway supplier selection, 2) to propose a supplier selection model for the decision-making process in railway supplier selection, and 3) to evaluate the effectiveness of the proposed model. This study proposes a supplier selection model for the railway industry. For this, the study has adopted a process-based research design involving three main phases as Planning and Analysis, Design and Development, and Testing and Evaluation to evaluate the proposed supplier selection model for the railway supplier selection. The relationship between the decision-making process and supplier selection requirements was framed within the MIT90s framework under the technology factor. Further, the study applies a rule-based technique for the multi-criteria decision-making process in selecting the potential suppliers from a railway information system prototype. The findings of this study were drawn primarily from quantitative data. For this purpose, survey questionnaires have been utilized for the data collection. Yet, the quantitative data were analyzed based on a reliability test by the validity of the proposed supplier selection model. In summary, the findings of the evaluations show a significant contribution to the body of knowledge of the decision-making process in information system and a solution to the industry practice that highlighted the most critical supplier selection criteria that need to be strategized with decision makers-stakeholders in railway supplier selection. The results of the reliability test show that all the five variables are found to have a significant coefficient, indicating that all the five constructs have a significant alpha value.